URGENSI LITERASI NUMERASI BAGI SISWA SD DALAM MENGHADAPI LEMAHNYA PEMAHAMAN KONSEP MATEMATIKA: KAJIAN BERBASIS LITERATUR - Ersa Apriyolasani; Dwi Avita Nurhidayah; Wahyudi Wahyudi (Universitas Muhammadiyah Ponorogo, 2026)
This article aims to discuss the importance of improving numeracy literacy skills for elementary school students in addressing the difficulties of understanding mathematical concepts, while considering the use of gadgets as a hindering factor. The objects of this study are the state of numeracy literacy and mathematical concept comprehension among elementary school students in Indonesia, particularly in the context of uncontrolled gadget usage at home. This study employed a literature review method, sourcing data from Sinta-accredited national journals, Scopus and Web of Science-indexed international journals, as well as official reports from the Ministry of Education and Culture (Kemdikbud), OECD, and PISA published within the last ten years. Data were systematically collected from various databases, such as Google Scholar, ERIC, Garuda, and Sinta, and subsequently analyzed using content analysis and thematic synthesis. The findings indicate a strong and reciprocal relationship between numeracy literacy and mathematical concept understanding, serving as a predictor of long-term academic success, as confirmed by Jordan et al. (2022) and supported by the findings of Purwaningrum et al. (2023) in the Edupedia journal. Meanwhile, the uncontrolled use of gadgets was found to undermine students' foundational numeracy skills in several ways: by consuming independent study time, reducing working memory, substituting numeracy tasks with entertainment media, and diminishing students' intrinsic learning motivation. This study asserts that improving numeracy comprehension is a critical necessity in education. Achieving this requires collaboration among various stakeholders. Teachers must employ instructional methods that are relevant to daily life contexts. Parents should also actively guide their children's learning and regulate their screen time. Furthermore, the government and policymakers must improve the curriculum and facilitate continuous professional development for teachers.